Photopic and scotopic light perception, related to outdoor lighting design - Bell, Michelle; Hasler, Fred (Kansas State University, 2011)
Current techniques in calculation, design of lighting, and measurement primarily focus on how the human eye perceives illumination photopically. What we know is that at night the eye primarily utilizes scotopic vision, with photopic vision to a lesser degree. Incorporation of scotopic analysis into the design process could provide many benefits related to human perception and overall system efficiency. It is important to first understand how the eye works, related to photopic and scotopic vision. The eye clearly views illumination differently, under a variety of circumstances. We need to be able to apply knowledge learned to identify changes in the way lighting designers go about their work. In order to verify calculations and theories we also need Illumination measurement devices to respond to the scotopic aspect of how we perceive illumination. Several studies have been performed over the past few years related to photopic and scotopic vision. These studies have suggested that the level of perceived illumination is quite different than originally believed. The spectral power density of light sources must be weighted by the photopic and scotopic response of the eye for a more realistic lumen output. By incorporating scotopic aspects into lighting calculations and measurement, it was found that in many cases we can accept significantly lower illumination levels. These lower levels also correspond directly to reduced energy consumption while providing for a more pleasing and preferred environment. In the spring of 2010 the City of Manhattan began an independent study of replacing the downtown street lighting. Their goal was to improve the perceived lighting and at the same time reduce the energy consumption and maintenance. Several high pressure sodium luminaires were replaced with LED of similar style so that a side by side comparison could be made. The department of Architectural Engineering at Kansas State University assisted in this study by taking illumination measurements, performing computer based calculations and conducting a survey to determine what the public thought about the proposed change. The results of the past work in this area and the recent study in downtown Manhattan have reinforced the fact that we need to change the standards and guidelines for lighting design, especially at night. Incorporating scotopic aspects into design will reduce energy consumption dramatically while providing a perceived illumination that is actually preferred by a vast majority of people.
Keywords: Photopic vision; Scotopic vision; LED; Light emitting diodes; Street lighting